Identification and characterisation of Botrylloides (Styelidae) species from Aotearoa New Zealand coasts - Berivan Temiz; Rebecca M. Clarke; Mike Page; Miles Lamare; Megan J. Wilson (New Zealand Journal of Marine and Freshwater Research, 2024)
Ascidians are marine filter‐feeder chordates. Botrylloides ascidians possess diverse biological properties such as whole‐body regeneration (WBR), hibernation/aestivation, blastogenesis, metamorphosis, and natural chimerism. However, the absence of distinctive morphological features often makes identification difficult. Botrylloides diegensis is an ascidian that has been misidentified in previous studies and is recorded in GenBank as Botrylloides leachii owing to the high morphological similarity between the sister species. More available sequences and strategies for identification would help resolve some of the confusion surrounding its ambiguous nature. We collected several Botrylloides samples from seven locations in Aotearoa New Zealand (Dunedin, Christchurch, Picton, Nelson, Whangateau, New Plymouth, and Invercargill) and barcoded the species based on Cytochrome Oxidase I, Histone 3, 18S, and 28S ribosomal RNA markers. Network and Bayesian trees confirmed the presence of three Botrylloides species: B. diegensis , Botrylloides jacksonianum, and Botrylloides affinis anceps.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Seasonal diet changes in elephant and impala in mopane woodland - Martine Kos; Arno J. Hoetmer; Yolanda Pretorius; Willem Frederik de Boer; Henjo de Knegt; C. C. Grant; Edward Kohi; Bruce Page; Mike Peel; Rob Slotow; Cornelis van der Waal; Sipke E. van Wieren; et al. (European Journal of Wildlife Research, 2012)

First record of the Australian ascidian Eudistoma elongatum in northern New Zealand - Peter J. Smith; Mike Page; Sean J. Handley; S. Margaret McVeagh; Merrick Ekins (New Zealand Journal of Marine and Freshwater Research, 2007)
A colonial ascidian was first reported by marine farmers in Houhora Harbour, Northland, New Zealand in early 2005 and subsequently found on oyster racks in Parengarenga Harbour and the Bay of Islands. The Northland ascidian was identified with a combination of morphological characters and DNA cytochrome c oxidase I (COI) sequence data, as Eudistoma elongatum , a species native to Australia, where it is found from northern New South Wales to Northern Queensland, and distinguished from Eudistoma circumvallatum , the only reported species in this genus from New Zealand. Ascidian larvae are weak dispersers and long distance dispersal of E. elongatum is likely to be enhanced by vectors such as oyster barges and/or movement of cultured oysters. In its native range, E. elongatum is restricted to areas with a minimum winter sea temperature of 16°C. Assuming similar biological limitations apply in New Zealand, the spread of E. elongatum might be restricted to northern New Zealand (north of latitude 37°S).

Aquaculture trials of the New Zealand bath‐sponge Spongia ( Heterofibria ) manipulatus using lanterns - Michelle Kelly; Sean Handley; Mike Page; Paul Butterfield; Bruce Hartill; Shane Kelly (New Zealand Journal of Marine and Freshwater Research, 2004)
A submarine lantern system was trailed in the aquaculture of explants of the endemic New Zealand bath‐sponge Spongia ( Heterofibria ) manipulatus (Demospongiae: Dictyoceratida: Spongiidae) at four New Zealand sites, two in the Marlborough Sounds and two off Coromandel Peninsula. The main objectives were to compare growth rates of explants at different sites, compare these with those of control sponges, and to assess the utility of these lanterns for the culture of this species. After a period of 13 months, sponges at exposed Bonne Point in the Marlborough Sounds were on average 73% larger in estimated volume than at the start of the experiments. Growth rates of explants at exposed Port Charles, Coromandel, showed no significant change over the study period, although positive growth over spring 2003 was evident. Sponge explants at sheltered Wairangi Inlet and Kennedy Bay, in the Marlborough Sounds and Coromandel, respectively, did poorly, with most explants regressing in size and becoming moribund. Growth rates varied considerably between individuals at each location. Implications of the growth rate characteristics of S . ( H .) manipulatus , and the design and construction of the aquaculture lantern, for the future commercial production of this species are discussed.